(untitled) (Oratio Directa, 2024)
Indonesia is known as one of the world's leading tobacco-producing countries. Clear regulation from upstream to downstream is required so that tobacco control benefits society while accounting for health protection, social life, cultural customs, and industrial interests. As a democratic country, Indonesia divides power among the executive, legislative, and judicial branches, and interaction between the executive and legislature occurs throughout the deliberation, decision-making, and ratification of laws. The prolonged and controversial deliberation of the Tobacco Bill, its multiplier effects, and accessible meeting records make it relevant for study through groupthink theory. This qualitative study uses a constructivist paradigm. Each member of the special committee represents a political party and expresses views according to the party's vision, mission, and ideology. The findings indicate that policy can become a political commodity, causing an urgent bill to proceed slowly and remain unresolved because of competing interests.